The Development of Independent Travel in China in the Future and Travel Agents’ Coping Strategies - Pan, Yulu (2010)
Abstract The purpose of this research is to understand the general trend of independent travel in China from tourists’ perspectives and what strategies travel agents should adopt to cope with the increased independent travel.